Effect of broccoli (Brassica oleracea) florets and stems as a fat replacer on the physicochemical and sensorial properties of chicken patties - Wei-Ai, Wei-Ai; Faridah, Mohd Razali; Asyrul-Izhar, Abu Bakar; Ab Aziz, Muhamad Faris; Kumar, Pavan; Sazili, Awis Qurni; Ismail-Fitry, Mohammad Rashedi (Journal of Meat Science, 2025)
This study aimed to evaluate the effects of replacing animal fat with various levels of broccoli (0, 25, 50, 75, and 100%) on the physicochemical and sensory properties of chicken patties. Fresh broccoli florets and stems were blanched and minced before being added to the patties’ formulation, and all samples were analysed for their physicochemical and sensorial properties. The highest significant (P<0.05) percentages of moisture, protein, and fibre content were noted as the broccoli incorporation increased especially in patties with 100% broccoli, at 61.85%, 11.38%, and 6.35%, respectively. The patty with the lowest (P<0.05) fat content was produced by fat replacement at 100% broccoli, with a fat content of 12.27% compared to the control at 20.48%. The textural properties of all samples showed no significant difference (P>0.05) in terms of hardness, cohesiveness, chewiness, and work of shearing. Nevertheless, the sensory analysis determined that patties with 75% and 100% broccoli were negatively affected, especially in colour, flavour, and overall acceptance. However, 25% and 50% broccoli were comparable to the control. In conclusion, broccoli may be used as a fat replacer for up to 25 to 50% in producing healthier chicken patties without jeopardizing their physicochemical and sensory properties.